ChemInform Abstract: Unveiling Latent α‐Iminocarbene Reactivity for Intermolecular Cascade Reactions Through Alkyne Oxidative Amination. Issue 42 (1st October 2013) - Mace, Nina; Thornton, Aaron R.; Blakey, Simon B.
Abstract The present protocol provides a metallonitrene/alkyne cascade which is terminated by ylide formation and [2, 3] Wittig rearrangement.